Does The Shariah Bank In Indonesia Through Financial Distress? - Sari, Maya Rizki; Yuri, Iftikar Arif (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This study aims to determine the potential of financial distress for Shariah Bank Industry Sector in Indonesia in the 2016-2018 period using the Zmijewski model. The data used in this study are secondary data on Sharia-based Banking in the 2016-2018 period, namely in the form of financial and annual reports from Muamalat Bank, BRI Syariah Bank, BNI Syariah Bank, Mandiri Syariah Bank, and BCA Syariah Bank. The final results of this study indicate that Sharia-based banking in the 2016-2018 period were classified into two categories, namely companies included in the Distress Area and Non-Distress Area categories. The results of the analysis showed that all sharia banks that were used as research samples consistently included in the Non-Distress Area category in the 2016-2018 period, the five companies were included in the healthy category and had no potential to go bankrupt. And the Sharia banking that can be categorized as the healthiest of the five Sharia Bank samples is BCA Syariah Bank, which in this case is stable away from the cut-off point below 0 or Z <0 that is above -3.5.